Talent Management in Engineering: A Review of Recruitment, Retention, and Development Strategies - Momeni, Nahid; Nazemi, Zahra (Management Strategies and Engineering Sciences, 2022)
This article provides a comprehensive narrative review of talent management strategies within the engineering sector, focusing on the key areas of recruitment, retention, and development. Given the increasing global demand for skilled engineers and the competitive nature of the engineering job market, effective talent management has become a critical strategic priority for organizations. The review synthesizes findings from existing literature, highlighting innovative recruitment practices, such as employer branding and the use of artificial intelligence, as well as retention strategies centered on career development, job satisfaction, and work-life balance. Furthermore, it examines development strategies that emphasize continuous learning and the integration of emerging technologies like virtual reality in training programs. The discussion explores the implications of these findings for engineering firms and HR practitioners, drawing comparisons with talent management practices in other industries and contributing to the broader theoretical understanding of talent management. The article concludes with practical recommendations and suggestions for future research, addressing gaps identified in the current literature.